The Impact of Green Economy Implementation on MSMEs in Musi Rawas District and its Implications on Business Growth - Nopa Dwi Saputra; Qautsu Quza Fitria Jannah; Fhemmy Lia Purnama Dewi; Siti Nur Khotimah; Bambang Irawan; Nadia Ulfa (Trescode Green Organization, 2025)
This study aims to analyze the impact of implementing green economy principles on micro, small, and medium enterprises (MSMEs) in Musi Rawas Regency and examine its implications for business growth. Green economy emphasizes resource efficiency, waste reduction, and environmental sustainability without ignoring economic growth. The method used in this study is a qualitative-descriptive approach with data collection through interviews, observations, and documentation studies of several MSME actors who have implemented environmentally friendly practices. The results of the study indicate that some MSMEs that adopt green economy principles, such as the use of environmentally friendly raw materials and good waste management, experience an increase in business image, customer loyalty, and cost efficiency in the long term. However, limited access to information, technology, and financing are major challenges in implementing a green economy widely. The implications of these findings indicate that with the support of appropriate policies and ongoing training, the green economy can be a significant driver of MSME business growth in the region. Therefore, synergy between the government, business actors, and financial institutions is needed to strengthen the green MSME ecosystem in Musi Rawas Regency.